2018
DOI: 10.1200/jgo.17.00216
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine for the Prevention of Chemotherapy-Induced Nausea and Vomiting: A Comparative Study From Sudan

Abstract: PurposeChemotherapy-induced nausea and vomiting (CINV) is a distressing adverse effect. Neurokinin-1 receptor antagonist (NK1RA)–containing regimens are the standard regimens for CINV prophylaxis in patients with cancer receiving highly or moderately emetogenic chemotherapy (HEC or MEC). NK1RA agents are expensive and were not registered in Sudan. Recently, regimens containing olanzapine, the available and affordable medication in Sudan, were introduced as another option. This study aimed to compare the effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The American Society of Clinical Oncology (ASCO) suggested the palliative care integrated early into oncology care is helpful for patients and families and complements the anticancer treatments [ 14 , 15 , 16 , 17 ]. The European Society of Medical Oncology (ESMO) proposed the term “patient-centered care” to defined care that aims to optimize the comfort, function, and social support of the patients and their families at all stages of the illness.…”
Section: Cancer Patients In Palliative Carementioning
confidence: 99%
“…The American Society of Clinical Oncology (ASCO) suggested the palliative care integrated early into oncology care is helpful for patients and families and complements the anticancer treatments [ 14 , 15 , 16 , 17 ]. The European Society of Medical Oncology (ESMO) proposed the term “patient-centered care” to defined care that aims to optimize the comfort, function, and social support of the patients and their families at all stages of the illness.…”
Section: Cancer Patients In Palliative Carementioning
confidence: 99%
“…Eleven studies ( 28 34 , 36 39 ) are randomized controlled experiments; one study ( 35 )is a prospective control study; and nine studies ( 28 31 , 33 , 34 , 37 39 ) compared 5 or 10 mg olanzapine with placebo, while three studies ( 32 , 35 , 36 ) compared the four-drug regimen with standard regimen; and 12 studies differed in the drugs used in the concurrent antiemetic regimens: a corticosteroid, 5-HT3 receptor antagonist, and NK1 receptor antagonist in seven studies ( 28 32 , 36 , 39 ) and a corticosteroid and 5-HT3 receptor antagonist in five studies ( 33 35 , 37 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies ( 31 39 ) reported the use of 10 mg olanzapine to prevent CINV; three studies ( 28 30 , 40 , 41 )reported the use of 5 mg olanzapine to prevent CINV; five studies ( 31 , 32 , 37 41 ) included HEC patients; two studies ( 29 , 33 )included MEC patients; and five studies ( 28 , 30 , 34 36 )included HEC and MEC patients. Of the five studies involving both HEC and MEC, only three studies ( 34 36 ) reported the results of HEC and MEC separately, and two studies were not enough for subgroup analysis; eight studies ( 28 , 29 , 31 35 , 37 ) reported adverse reactions including sedation, Table 2 provides the procedures of each study to evaluate the sedative effect of olanzapine; 11 studies ( 28 34 , 36 39 ) are randomized controlled experiments; 1 study ( 35 ) is a prospective control study ( 40 , 41 ); 9 studies used a double-blind placebo-controlled approach; and 3 studies ( 32 , 35 , 36 ) were unclear on blind methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing duplicate records and adding records identified from included trials, 178 records underwent level 1 screening. A total of 34 full-text articles were assessed for eligibility through level 2 screening, at which points 6 were excluded with reason-three were not a randomized controlled trial [36][37][38], one did not investigate olanzapine in the CINV setting [39], and two did not have an appropriate treatment regimen for inclusion in our review [40,41]. Of the remaining 28 articles, 25 randomized controlled trials had extractable data and were included in this systematic review and metaanalysis(Appendix 4 Electronic Supplementary Material).…”
Section: Included Studiesmentioning
confidence: 99%